Castle Simões Lopes - a disregard with history and public money in Pelotas/RS - Torres, Ariela da Silva (Universidade Estadual de Campinas, 2015)
Pelotas, a city in the south of Brazil, is a local renowned by its cultural quality in many sectors. The city has national notoriety by its heritage, reflected on architecture. There are many architectural examples that characterize the great diversity of historic buildings, and also the political influence that the region had during the twentieth century. The Simoes Lopes Castle is a representative example of the grandiosity in the past. This fortress became a property tumbled, that belongs to the state, and should ensure preservation and conservation. However, nowadays, this castle is idle urban space, a place of illicit activities and degraded architecture. Owing to its historical significance and architectural for the city, this castle was chosen as the case study, in order to collaborate with municipal and state government for the next process of intervention, and improve the life cycle of the building, through quality and scientific basis. This article is divided into two phases. The first phase was a survey of visual and photographic data from the castle facades. And the second was composed by data analyses and suggestions for improvements. It is important to consider that these numerous restoration work already undertaken, has dramatically increased the repair values, increasing spending public, that could have been avoided, and also creating an impossible environment to society conviviality.